Speech and thought in Latin war narratives : words of warriors - Adema, Suzanne M. (Amsterdam studies in classical philology, 2017)
In 'Speech and Thought in Latin War Narratives', Suzanne Adema offers linguistic and narratological tools to analyse and interpret narratorial choices in speech and thought representation in Latin narratives. Her approach combines insights from (cognitive) linguistic and narratological theories and has been tested and adjusted through corpus based research (Caesar, Vergil, Sallust). 0The approach is a useful tool to unveil rhetorical uses of speech and thought representation in Latin war narrative by means of close readings of Caesar?s 'Bellum Gallicum' 1 and 7, and Vergil?s 'Aeneid' 11 and 12. Focusing on the attitudes of the narrators towards war, Adema provides new insights into these texts and offers linguistic and narratological contributions to literary and historical discussions about the 'Bellum Gallicum' and the 'Aeneid'.